UNIFIED PROCEDURE FOR BALANCING THE REDOX REACTION THROUGH THE ION-ELECTRON METHOD - Lavado Soto, Mooner (2005)
The oxidation-reduction reactions, typically known as “redox reactions”, are the most important group of chemical reactions. This study proposes a unified procedure for balancing those reactions through an ionelectron method, either in acid or basic medium. Traditionally, balancing is carried out through different stages in most parts of the process.